Sincronização do estro em pacas (Cuniculus paca L.): Possíveis impactos sobre parâmetros reprodutivos e produtivos - Ribeiro, Vânia Maria França; Satrapa, Rodolpho; Diniz, Jefferson Viana Alves [UNESP]; Fêo, Haline Ballestero [UNESP]; Flórez, Luis Mauricio Montoya [UNESP]; Satrapa, Rafael Augusto; Oba, Eunice [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2017)
Estrus synchronization is a reproductive biotechnology used to improve artificial insemination or pairing through the manipulation of the estrous cycle at a desirable time. Employing this technique in captive pacas (Cuniculus paca L.) is important because it creates expectation of meeting the demand for paca meat and, consequently, reduces poaching. Thus, this research aims to verify the effect of a progestogen implant associated with two doses of eCG on the synchronization and induction of fertile estrus. Twenty-seven adult pacas were used, 18 non-pregnant females and nine males, divided into three groups. G1 and G2 females groups (treatments) received 1.5 mg Norgestomet and were injected intramuscularly, seven days later, with 0.13 mg of prostaglandin. After 24 hours the implants were removed and the animals immediately received 25 IU and 50 IU of ECG intramuscularly, respectively. The mating of the three groups took place on the same days. G3 females’ group (control) showed estrus on different days after D0. Females under treatment displayed estrus only after removing the implant (D8). G1, G2, and G3 pregnancy rates were 100%, 66%, and 50%, respectively. Regarding births per parturition, 100% of G1 and G3 produced one offspring, while 50% of G2 produced two. Progestogen in the form of subcutaneous implants was effective in mimicking the luteal phase of the estrous cycle. After removal, implants favored the occurrence of a fertile estrus. As a conclusion, further studies must be conducted in order to establish in-depth possible association between 50 IU of eCG, and the occurrence of twin pregnancies.
Synchronization of estrus in paca (Cuniculus paca L.): Possible impacts on reproductive and productive parameters
Keywords: Heat; Progestin; Rodent; Synchronization